Analisis Perkembangan Bahasa Ekspresif Anak Usia 4–5 Tahun di Lingkungan Multibahasa - Kiki Nuraini; Dewi Ayu Pramita (Jurnal Pendidikan Bahasa dan Anak Usia Dini, 2025)
This study analyzes the development of expressive language skills in children aged 4 to 5 years living in multilingual environments. The research aims to understand how exposure to multiple languages influences the expressive abilities of young children. A qualitative approach was applied, involving observation and structured interviews with parents and educators. Findings indicate that children in multilingual settings exhibit varied vocabulary usage and code-switching behaviors, with some delays in expressive fluency compared to monolingual peers, yet with enhanced pragmatic skills. The study highlights the importance of supportive linguistic environments and tailored educational strategies to foster optimal language development. These findings have implications for educators, speech therapists, and parents in managing multilingualism during early childhood.